2016
DOI: 10.1016/j.virol.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Construction and characterization of a full-length cDNA infectious clone of emerging porcine Senecavirus A

Abstract: A full-length cDNA infectious clone, pKS15-01-Clone, was constructed from an emerging Senecavirus A (SVA; strain KS15-01). To explore the potential use as a viral backbone for expressing marker genes, the enhanced green fluorescent protein (EGFP)-tagged reporter virus (vKS15-01-EGFP) was generated using reverse genetics. Compared to the parental virus, the pKS15-01-Clone derived virus (vKS15-01-Clone) replicated efficiently in vitro and in vivo, and induced similar levels of neutralizing antibody and cytokine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 29 publications
3
46
0
2
Order By: Relevance
“…Several recent studies have reported on the pathogenicity of SVA [5,7,[21][22][23][24]. Theoretically, all SVA strains isolated from diseased pigs have pathogenic potentiality.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have reported on the pathogenicity of SVA [5,7,[21][22][23][24]. Theoretically, all SVA strains isolated from diseased pigs have pathogenic potentiality.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with DNA virus, it's discovered that RNA virus, such as influenza virus, coronaviruses, exists a highly evolution rate [27e30]. Previous studies revealed that the prototype SVA isolate, namely SVV-001, was isolated in 2001 [31], and due to its selective tropism for human tumor cells, the virus was developed as an oncolytic agent [32].However, the basic viral pathogenesis was not detected accurately. In this study, the synonymous codon usage of the SVA was analyzed to better understand the SVA evolution, especially the interplay between the viruses and the immune response [33].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, SVV has been experimentally confirmed to cause vesicular disease in piglets using a contemporary 2015 SVV field isolate from the USA (Chen et al, 2016;Montiel et al, 2016). The clinical signs associated with the vesicular manifestation of SVV infection are indistinguishable from those caused by foot-and-mouth disease (FMD), swine vesicular disease (SVD) and vesicular stomatitis (VS) with pigs presenting with vesicles on the snouts and coronary bands, lameness, anorexia, lethargy, and fever and exclusion of FMD, SVD or VS on affected farms is required by the animal health authorities.…”
Section: Textmentioning
confidence: 99%